PERANCANGAN APLIKASI ANDROID PENGUCAPAN HURUF HIJAIYAH SEBAGAI MEDIA PEMBELAJARAN FAST QURAN MENGGUNAKAN FLUTTER - Faishal Arif Wibowo; Hartatik (LPPM STMIK El Rahma Yogyakarta, 2020)
Technological developments provide enormous benefits to all circles of society. In terms of education, it has also taken advantage of the development of android. Likewise in the field of religious education. Technology really supports the learning process among vulnerable ages, one of which is android as a medium for learning to read the Al-Qur'an. In countries that are predominantly Muslim, in fact there are still many who cannot read the Al-Qur'an. Based on PTIQ Jakarta's research, approximately 50 to 60 percent of Muslims cannot read the Qur'an. From this research, it was found that almost half of Indonesia's Muslim population could not read the Al-Qur'an. This condition is very concerning. By taking advantage of technological developments, utilizing Android and seeing existing realities, prompted me to design this application to make it easier for users to learn to pronounce hijaiyah letters correctly according to the character of the letters and according to the place where the hijaiyah letters came out. With this application to support the learning process in Fast Quran. This application uses the Flutter framework with the Dart programming language and is developed with Visual Studio Code.